Sonchus asper (L.) Hill extracts: phytochemical characterization and exploitation of its biological activities by loading into nanoformulation - Parisi, Valentina; Santoro, Valentina; Faraone, Immacolata; Benedetto, Nadia; Vassallo, Antonio; De Tommasi, Nunziatina; Milella, Luigi; Nesticò, Antonio; Maselli, Gabriella; Fadda, Anna Maria; Caddeo, Carla (Frontiers in Plant Science, 2024)
Introduction The current investigation presents a two-fold approach to rediscovering the potential of Sonchus asper as a wild edible plant, both in its raw extract form and as a nanoformulated product. Furthermore, the study aimed to promote the valorization of traditional dishes and contribute to biodiversity conservation and sustainable use of S. asper, thus enhancing economic profits. Methods Liquid chromatography-mass spectrometry analyses were conducted to characterize the metabolite profile of the raw and cooked leaf extracts, and the extract from discarded leaves. The antioxidant activity, the hypoglycaemic effect and the incorporation into liposomes were evaluated. Results 38 compounds and 6 essential amino acids were identified. The incorporation into liposomes maximized the health-promoting properties for potential pharmaceutical or food applications. Discussion The commercialization of S. asper could: (i) contribute to improving the well-being of rural and urban communities, being S. asper a wild edible plant available at low cost, environmentally friendly, resilient, and adaptable; (ii) generate landowner economic returns.